Determinan dan Strategi Pencegahan Stunting Pada Anak di Negara Berkembang : Literatur Review - Mashatim; Ilham Akbar; Nurul Amirah Ramadhani Lembah; Sudirman; Ahmad Yani (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Inequality in child health status in developing countries remains a serious public health issue, particularly because stunting not only reflects chronic undernutrition but also indicates disparities in social, economic, educational, sanitation, food security, and access to basic health services. This condition affects physical growth, cognitive development, future productivity, and the overall quality of human resources. This study aims to analyze the determinants contributing to stunting among children in developing countries and to identify relevant, comprehensive, and sustainable prevention strategies. The method used in this study is a literature review by examining various scientific articles, reports from health organizations, and policy documents discussing the causal factors and preventive interventions for stunting. The literature was selected based on topic relevance, recency of information, source quality, and its relevance to the public health context in developing countries. The findings indicate that stunting is influenced by multidimensional factors, including inadequate maternal and child nutritional intake, suboptimal infant and young child feeding practices, recurrent infectious diseases, low maternal education, poverty, limited access to clean water and sanitation, and poor utilization of basic health services. Stunting prevention strategies need to be implemented through both nutrition-specific and nutrition-sensitive approaches, such as fulfilling maternal nutritional needs during pregnancy, promoting exclusive breastfeeding, providing adequate complementary feeding, micronutrient supplementation, immunization, growth monitoring, sanitation improvement, strengthening household food security, and community-based health education. Scientifically, this study finds that stunting prevention cannot be achieved solely through nutritional interventions but requires the integration of cross-sectoral policies involving the health, education, social, food, economic, and environmental sectors. Therefore, stunting management in developing countries should be directed toward improving structural determinants and family health behaviors simultaneously so that its impact becomes more effective, equitable, and sustainable.